“Acconciar grotti” alla villa di Pratolino e nei giardini del castello dei Gondi a Noisy-le-Roi - Calafati, Marco (Opus Incertum, 2019)
The “Libro delle bestie di Firenze e fabbrica di Pratolino” of 1575 which is kept at the University of Pennsylvania in Philadelphia, includes the name of the Gondi as administrators of the accounts of the construction. In the same period in Noisy-le-Roi, on the hill north of the valley of Versailles and on the edge of the Marly forest, Alberto Gondi (1522-1602), Duke of Retz and Marshal of France, right arm of the Queen mother, commissioned the construction of a castle with large gardens, which was later destroyed. In Noisy, Alberto Gondi began the construction of a grotto represented in a series of engravings by Jean Marot (1619-1679), but the recent archaeological excavations carried out in 2017 by Bruno Bentz, show that the architectural plan was possibly inverted. In the creation of the grotto, evidence was found of Florentine.